Korea’s Capital Market Promotion Policies: IPOs and Other Supplementary Policy Experiences - 김우찬 (14185, 2015)
This paper studies a series of capital market promotion policies Korea pursued over a 30-year period during its development era (1960s - 1980s). The purpose of this paper is twofold. The first purpose is to understand the policy approaches Korea took, and